Recent applications of analytical techniques for quantitative pharmaceutical analysis: A review - Bonfilio, Rudy [UNESP]; de Araújo, Magali Benjamim; Salgado, Hérida Regina Nunes [UNESP] (My University, 2010)
The intension of this paper was to review and discuss some of the current quantitative analytical procedures which are used for quality control of pharmaceutical products. The selected papers were organized according to the analytical technique employed. Several techniques like ultraviolet/visible spectrophotometry, fluorimetry, titrimetry, electroanalytical techniques, chromatographic methods (thin-layer chromatography, gas chromatography and high-performance liquid chromatography), capillary electrophoresis and vibrational spectroscopies are the main techniques that have been used for the quantitative analysis of pharmaceutical compounds. In conclusion, although simple techniques such as UV/VIS spectrophotometry and TLC are still extensively employed, HPLC is the most popular instrumental technique used for the analysis of pharmaceuticals. Besides, a review of recent works in the area of pharmaceutical analysis showed a trend in the application of techniques increasingly rapid such as ultra performance liquid chromatography and the use of sensitive and specific detectors as mass spectrometers.
Keywords: Analytical techniques; Pharmaceutical analysis; Pharmaceutical quality control; camptothecin; chlordiazepoxide; chlorzoxazone; clonazepam; diazepam; diltiazem; doxepin; drug; flunarizine; fluphenazine; hydrochlorothiazide; hydroxyzine; ibuprofen; indapamide; irinotecan; lamotrigine; lumiracoxib; multi walled nanotube; nicardipine; nitrazepam; nordazepam; perazine; pregabalin; promazine; rosiglitazone; stavudine; topotecan; unindexed drug; verapamil; xipamide; amperometry; analytical research; capillary electrophoresis; chromatography; conductometry; coulometry; differential pulse voltammetry; drug degradation; drug determination; drug mechanism; drug oxidation; drug selectivity; Fourier transform infrared photoacoustic spectroscopy; gas chromatography; high performance liquid chromatography; human; infrared spectroscopy; limit of detection; medical literature; performance measurement system; polarography; potentiometry; quality control; review; sensitivity and specificity; spectral sensitivity; spectrofluorometry; spectrometry; thin layer chromatography; titrimetry; ultra performance liquid chromatography; ultraviolet spectrophotometry